Effective Innovation Policies for Development: Uganda - Ecuru, Julius; Kawooya, Dick (The Global Innovation, 2015)
As a landlocked country, Uganda’s economy is largely dependent on neighbouring countries for access to and participation in global economic activities. Until recently, following two decades of armed conflict that lasted from 1966 to 1986, Uganda relied on Kenya for the majority of its consumer goods. Since 1986 the country has focused its efforts on recovery, with socioeconomic activities and public policies geared towards development in key sectors such as roads, energy, agriculture, health, education, and security. Uganda’s recent progress in the Global Innovation Index (GII) is the result of nearly 30 years of consistent and relatively predictable socioeconomic policies aimed at transforming the country from a peasant society to a middle-income economy by the year 2040.
Keywords: Innovation Policies; development; economy